Bioecological analysis of alien faction in urban floras of Northern Azov (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The article discusses the adventive component in urban floras of Northern Azov (on the example of Berdyansk, Primorsk and Genichesk). The research found that the adventive fraction of urban floras Northern Azov has 227 species that belong to 165 genera and 52 families, representing more than a quarter of the number of species of urban floras. It represents a significant clogging of the studied cities by alien plants species. Biomorphological spectrum of life forms in studied flora reflects the character of the adaptations of adventive plants to a set of certain environmental, physical and geographical conditions. Our ecological and biological analysis of the adventive fraction in model towns in Northern Azov points to the processes of "therophytization" and "xerophytization" in flora.
Keywords: adventive fraction, urban flora, biomorphes, ecomorphes, Northern Azov.